Surgical Management of Acute Extradural Hematoma in Bauchi Nigeria: Challenges and Outcomes - O. Ogunleye, Olabisi; B. Ogunleye, Oluchukwu; M. Muhammed, Muhammed; M. Muhammad, Adamu (Clinical Medicine And Health Research Journal, 2023)
Introduction: Acute extradural hematoma (EDH) is a neurosurgical emergency and can be life threatening in many occasions. It is defined as a collection of blood within the dura matter and inner table of the skull. We aimed to study the incidence and outcomes of acute EDH managed in our facility Materials and Methods: Ninety seven consecutive patients managed surgically for acute extradural hematoma (EDH) within 4 years. Demographic data, time of presentation, GCS score and Glasgow outcome score (extended) were analyzed. Results: Acute EDH has yearly occurrence of 24.3 per year. Out of 97 cases 89 % were male and 11% were female. The male and female ratio was 7.8: 1. Commonest age group was 21 to 30 years. Commonest mode of injury was Road traffic Accident 59.8%, followed by Assaults. Most common clinical presentation was headache (74.2%) followed by altered consciousness (38%). In this study of 97 cases of EDH, frontal site was involved in 26% followed by parieto-temporal region in 22%. 90% of the patients had favorable outcome while the mortality rate was 3.1%. Conclusion: Acute Extradural hematoma is a neurosurgical emergency where the admitting GCS score and early surgical intervention is associated with favorable outcome. Legislation and optimal social amenities will reduce the incidence of traumatic brain injury and improve the surgical outcome of acute EDH..